2013
DOI: 10.1097/gme.0b013e31826560da
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunction in women on adjuvant endocrine therapy after breast cancer

Abstract: Our findings suggest that sexual dysfunction in aromatase inhibitor-treated women is a greatly underestimated problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
2
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(88 citation statements)
references
References 35 publications
3
70
2
6
Order By: Relevance
“…Emerging data suggest that although both selective estrogen receptor modulators (e.g., tamoxifen) and the aromatase inhibitors (AIs) may affect sexual function, the risk to sexual health may be greater with the AIs. This was shown in a study by Baumgart et al in which more than 80 women taking tamoxifen or an AI were compared with women without breast cancer (controls) [37]. Among women taking an AI, significantly higher rates of sexual dysfunction were reported compared with both those taking tamoxifen and controls in the area of lubrication issues (74% vs. 40% and 42%, respectively), dyspareunia (57% vs. 31% and 21%), and global dissatisfaction with their sex lives (42% vs. 17.8% and 14%).…”
Section: Medical Therapymentioning
confidence: 97%
“…Emerging data suggest that although both selective estrogen receptor modulators (e.g., tamoxifen) and the aromatase inhibitors (AIs) may affect sexual function, the risk to sexual health may be greater with the AIs. This was shown in a study by Baumgart et al in which more than 80 women taking tamoxifen or an AI were compared with women without breast cancer (controls) [37]. Among women taking an AI, significantly higher rates of sexual dysfunction were reported compared with both those taking tamoxifen and controls in the area of lubrication issues (74% vs. 40% and 42%, respectively), dyspareunia (57% vs. 31% and 21%), and global dissatisfaction with their sex lives (42% vs. 17.8% and 14%).…”
Section: Medical Therapymentioning
confidence: 97%
“…There is increasing awareness of the prevalence of genitourinary side effects of endocrine therapy and their potential impact on sexual functioning [Chin et al 2009;Baumgart et al 2013;Baumgart et al 2011;Schover et al 2006;Donovan, 2012]. It has been reported that up to 50-75% of breast cancer survivors experience one or more genitourinary symptoms [Ganz et al 1998;Trinkaus et al 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Sexual sequelae from aromatase inhibitors can be severe and debilitating (vaginal, vulvar, and/or clitoral dryness). 129 Management can include reinforcing and encouraging nonpenetrative sex if non-estrogen vaginal products to ease dyspareunia are insufficient.…”
Section: Radiation Chemotherapy and Hormonal Considerationsmentioning
confidence: 99%